Expression and regulation of the immune modulatory enzyme indoleamine 2,3-dioxygenase (IDO) in human epithelial cells - Aldajani, Wejdan/WA (2016)
Epithelial cells (ECs) are key players in the modulation of immune responses in addition to its main role as a barrier against external stimuli. Upon stimulation with pathogens/allergens, airway ECs can produce a wide range of innate mediators that recruit and activate immune cells which play a key role in maintaining immune homeostasis in the lungs. One such mediator is indoleamine 2,3- dioxygenase (IDO), which is a rate-limiting enzyme involved in tryptophan (TRP) catabolism. IDO plays a role in the modulation of immune responses to antigenic challenges and also acts as an anti-microbial factor. Therefore, the main aim of this project was investigating IDO expression, immune regulatory function and regulation pattern in human airway ECs in response to clinically relevant toll-like receptor (TLR) ligands and allergen extracts. This was done in 2D cultures and in a 3D model using ECs from healthy and diseased donors. The data clearly demonstrated that ECs constitutively produce IDO which is up-regulated in response to IFN-. However, I have shown for the first time, that IDO production and activity is down-regulated in response to TLR ligands and allergen extracts. Indeed, using gene silencing, I demonstrated that ‘resting’ ECs (i.e. with high IDO expression) can suppress T cell activation in an IDO-dependent manner, but this regulatory function is lost in response to TLR agonists mimicking bacterial or viral infections. These data provide new insight into how ECs, as part of their function in maintaining immune homeostasis in airways, can influence downstream innate and adaptive immune responses through the production of IDO. In this study, I also focused on developing an immunocompetent 3D model of human airway ECs in regards to produce certain in vivo characteristics. In addition, the effect of EC differentiation state and cross-talk with other cells on IDO activity was investigated. My data showed that EC lines and primary human bronchial ECs (pHBECs) could be differentiated at the air-liquid interface (ALI) and form ZO-1 tight junctions. Moreover, ECs had higher TEER values when co-cultured with fibroblasts than when cultured alone which indicates that fibroblasts facilitate EC differentiation, highlighting the importance of paracrine interactions and cross-talk between cells in maintaining EC barrier function. Moreover, the data showed differential regulation of IDO activity on the basis of culture conditions which suggest that differentiation and co-culture status might affect the orientation and expression pattern of TLRs. Furthermore, our data in regards to IDO regulation in physiological and pathophysiological settings demonstrated the differential regulation of IDO and considerably different IDO basal levels in healthy cells compared with diseased cells, emphasizing the immunosuppressive role of IDO. In conclusion, these advances in the understanding of IDO expression and regulation in different tissue/cell types in health and disease could contribute to delineating the potential role of IDO in inflammatory responses in different pathologies and enable the development of novel IDO-targeted therapeutic strategies.